2014
DOI: 10.1002/2013ja019668
|View full text |Cite
|
Sign up to set email alerts
|

Quiet time short‐period and day‐to‐day variations in E × B drift studied using 150 km radar echoes from Gadanki

Abstract: In this paper we present short-period and day-to-day variations in E × B drift during low solar and magnetically quiet conditions, based on radar observations of daytime 150 km echoes from Gadanki, India. Short-period (<100 min) variations in E × B drift show amplitude as large as 7 m s À1 and display large day-to-day variation. Spectral analysis reveals that drift velocity fluctuations consist of several components of short periods in the range of 4-100 min. Among these periods, the most frequently occurring … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 37 publications
1
7
0
Order By: Relevance
“…These high‐resolution observations, while presenting the well‐known morphology of forenoon descent and afternoon ascent of the echoing region, illustrate quasiperiodic and sometimes highly complex variations of echo SNR indicating the role of complex forcing on the echoing phenomenon. The quasiperiodicity is found to be 5–15 min consistent with earlier observations from Gadanki (Patra, 2011; Pavan Chaitanya et al, 2014). On some occasions, the echoing region also shows multiple thin layers akin to those observed from Jicamarca (e.g., Chau & Kudeki, 2013).…”
Section: Observational Resultssupporting
confidence: 90%
“…These high‐resolution observations, while presenting the well‐known morphology of forenoon descent and afternoon ascent of the echoing region, illustrate quasiperiodic and sometimes highly complex variations of echo SNR indicating the role of complex forcing on the echoing phenomenon. The quasiperiodicity is found to be 5–15 min consistent with earlier observations from Gadanki (Patra, 2011; Pavan Chaitanya et al, 2014). On some occasions, the echoing region also shows multiple thin layers akin to those observed from Jicamarca (e.g., Chau & Kudeki, 2013).…”
Section: Observational Resultssupporting
confidence: 90%
“…It is noticed from their observations that, on an average, the vertical drifts are close to 0 or negative ∼1500 LT in June and July months and show decreasing trend around this time. Note that the decreasing trend in afternoon hours in months other than June solstice (e.g., December month) was not observed by both Pavan Chaitanya et al () and Patra et al (). Thus, these case studies give credence to the presence of westward Sq electric fields in afternoon hours during June solstice in solar minimum period.…”
Section: Discussionmentioning
confidence: 73%
“…These measurements have been extensively used over the Peruvian sector (Hui & Fejer, ). Over the Indian sector, such measurements of the vertical drifts over Gadanki (13.5°N, 79.2°E, dip latitude 6.5°N) are reported by Pavan Chaitanya et al () and Patra et al (). Patra et al () reported the vertical drifts for 4 days during July–August 2009 that indicate downward trend at ∼1500 LT. As the radar observational time was limited to ∼1500 LT, the westward Sq electric field could not be ascertained on most of the cases beyond this local time.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…These drift values (Patra et al, 2012(Patra et al, , 2014 are larger than the values derived in the present study. Using the same technique as Patra et al (2012Patra et al ( , 2014, the forenoon mean value of vertical drifts were found to be varying around 11-14 and 24-43 m/s during January and February 2009 (Chaitanya et al, 2013(Chaitanya et al, , 2014. For a high solar activity period, Anderson et al (2009) inferred the vertical drift pattern from the EEJ measurements for Indian longitudes during winter solstice and equinoxes.…”
Section: Discussion and Summarymentioning
confidence: 99%